Analysis of the scientific production of the Brazilian Antarctic Program - Araújo, Paula Carina de; Pinho, Roberto Dantas de; Kaled, Andrea Cancela da Cruz (Universidade Federal do Rio Grande do Sul, Faculdade de Biblioteconomia e Comunicação, Programa de Pós-Graduação em Ciência da Informação (Porto Alegre/RS), 2024)
This article analyzes the scientific production of the Brazilian Antarctic Program based on related production and connection indicators. It develops an exploratory and bibliometric research in seven stages. It uses data obtained from the Brazilian Navy Archive, public data from the National Council for Scientific and Technological Development, the Lattes Curriculum, the ORCiD, and the Global Research Identifier Database as data sources for identifying program scientists that led to a total of 3660 identified names. The Lens, Scopus, and Web of Science databases were used to collect data from the scientific production identified through this research. It presents the analysis of 1242 articles. In the year 2021, the biology area and the scientific journal Polar Biology, from Germany, present the highest number of publications. The University of São Paulo also stands out by the number of publications. The first most frequent word is Antarctic and the main collaboration relationship takes place between Brazil and the United States. The analysis revealed the solid and strategic development of the program, its maturity, and the important contribution of brazilian science to Antarctic research. The indicators and their context help to reflect the program's path towards consolidation of scientific information management for the promotion of scientific policies. The synthesis of the presented results shows that investments in research projects have been applied in research and scientific knowledge that has impacted Antarctic science. Analisa a produção científica do Programa Antártico Brasileiro a partir de indicadores de produção e ligação a ela relacionados. Desenvolve uma pesquisa exploratória e bibliométrica em sete etapas. Utiliza os dados obtidos por meio do Arquivo da Marinha do Brasil, dados públicos do Conselho Nacional de Desenvolvimento Científico e Tecnológico, o Currículo Lattes, o ORCiD e a Global Research Identifier Database como fontes de dados para a identificação dos pesquisadores do programa, o que ...